2019
DOI: 10.1007/s11262-019-01718-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis for virulence determinants in feline herpesvirus type-1 isolates

Abstract: Feline herpesvirus type 1 (FHV-1) is a widespread cause of respiratory and ocular disease in domestic cats. A spectrum of disease severity is observed in host animals, but there has been limited prior investigation into viral genome factors which could be responsible. Stocks of FHV-1 were established from oropharyngeal swabs obtained from twenty-five cats with signs of infection housed in eight animal shelters around the USA. A standardized numerical host clinical disease severity scoring scheme was used for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The severity and symptoms of FHV-1 infection are not relative to the viral genome variants, and it is most likely due to other factors such as host response 30 . Therefore, the different pathological changes of No.…”
Section: Discussionmentioning
confidence: 99%
“…The severity and symptoms of FHV-1 infection are not relative to the viral genome variants, and it is most likely due to other factors such as host response 30 . Therefore, the different pathological changes of No.…”
Section: Discussionmentioning
confidence: 99%
“…The ocular immunotherapy studies reported here utilized cat natural and experimental [28] FHV-1 infection models, which have been shown to recapitulate many of the clinical abnormalities associated with HSV-1 ocular infection in humans [29,30]. Recurrent ocular disease in cats is a common manifestation of chronic infection with FHV-1 [31][32][33][34].…”
Section: Plos Onementioning
confidence: 99%
“…The use of novel techniques such as NGS to evaluate ocular surface microbiota in veterinary ophthalmology remains in its infancy. Emerging researchers in our field have collaborated with leading microbiome experts to identify the presence of distinct, diverse, and stable microbial communities inhabiting the ocular surface of cats, dogs, and horses 13,14,42,43,55‐57 . While new opportunities arise, the usefulness and application of microbiome data in the veterinary clinic has yet to be determined, as considerable research remains for this objective to become a reality.…”
Section: Conclusion and Recommendations For The Futurementioning
confidence: 99%